(untitled) (Advances in Civil and Architectural Engineering, 2021)
The need for the introduction of trams in Osijek in the late 19th century was largely due to the poor connectivity between the areas of the city and the growing development of the city. Tram transport was an extremely important step in connecting and modernizing the city and a key step in the integration of the still unconnected areas of the city, a role it has played throughout history. From its beginnings, the residents of Osijek have been intricately connected to the tram, which has had a role in the modernization of the city and is today regarded as a symbol of the city. As a means of public transport, in Croatia, the tram is now used only in Zagreb and Osijek. Today, many cities around the world have reintroduced trams as a public transport system, and Osijek is one of the few “small” cities that can boast of its continuous existence and expansion. This paper describes the development and current state of tram traffic in Osijek as a contribution to the celebrations of the anniversary of the introduction of the electric tram in the city.